Magnetic resonance imaging detects progression of lung disease and impact of newborn screening in preschool children with cystic fibrosis - Stahl, Mirjam; Steinke, Eva; Gräber, Simon Y.; Joachim, Cornelia; Seitz, Christoph; Kauczor, Hans-Ulrich; Eichinger, Monika; Hämmerling, Susanne Hedwig; Sommerburg, Olaf; Wielpütz, Mark Oliver; Mall, Marcus A. (American journal of respiratory and critical care medicine, 2021)
Rationale: Previous cross-sectional studies have demonstrated that chest magnetic resonance imaging (MRI) is sensitive to detect early lung disease in infants and preschool children with cystic fibrosis (CF) without radiation exposure. However, the ability of MRI to detect the progression of lung disease and the impact of early diagnosis in preschool children with CF remains unknown. - - Objectives: To investigate the potential of MRI to detect progression of early lung disease and impact of early diagnosis by CF newborn screening (NBS) in preschool children with CF. - - Methods: An annual MRI was performed from diagnosis over 4 years in a cohort of 96 preschool children with CF (age, 0-4 yr) who received concurrent diagnoses on the basis of NBS (n = 28) or clinical symptoms (n = 68). MRI scans were evaluated using a dedicated morphofunctional score, and the relationship between longitudinal MRI score and respiratory symptoms, pulmonary exacerbations, upper airway microbiology, and mode of diagnosis was determined. - - Measurements and Main Results: The MRI global score increased in the total cohort of children with CF during preschool years (P < 0.001) and was associated with cough, pulmonary exacerbations (P < 0.0001), and the detection of Staphylococcus aureus and Haemophilus influenzae (P < 0.05). MRI-defined abnormalities in lung morphology—especially airway wall thickening/bronchiectasis—were lower in children with CF diagnosed by NBS than in children with clinically diagnosed CF throughout the observation period (P < 0.01). - - Conclusions: MRI detected progression of early lung disease and benefits of early diagnosis by NBS in preschool children with CF. These findings support MRI as a sensitive outcome measure for diagnostic monitoring and early intervention trials in preschool children with CF. - - Clinical trial registered with www.clinicaltrials.gov (NCT 02270476).
Gesehen am 15.01.2022